Reduction of road traffic accidents among young drivers through University and Vocational studies - Darabi Golshani, Ali Mohammed; Nikraz, Hamid; Nikravan, Z. (International Association of Technology, Education and Development (IATED), 2010)
World Health Organisation (WHO) statistics are alarming as over 3000 people lose their lives every day in road traffic related accidents. This is approximately equivalent to a 9/11 disaster every day. According to the Australian Institute of Health and Welfare (AIHW) in 2003 premature mortality was responsible for 41,032 Years of potential Life Lost (YLL) among young Australians aged 15-24 years. According to the report, injuries were the leading cause of premature mortality and accounted for two thirds of the total YLL. Road traffic accidents were responsible for 29% of the YLL, while suicide and self-inflicted injuries accounted for 21%. According to the report from the NSW Roads and Traffic Authority, young drivers represent one quarter of the Australian road deaths, but are only 10-15% of the licensed driver population. These facts and figures are astonishing and it is vital that further measures are introduced to tackle road traffic safety.One alternative method that has not been widely incorporated in today’s society and could successfully work towards tackling road traffic safety is the implementation of road safety education in Universities and Vocational institutions. This paper would examine a proposal for the introduction of new road safety and traffic accident prevention unit within first year Engineering Foundation program at Curtin University of Technology. Such a unit would enable students to think strategically and critically and take into consideration road safety and traffic prevention issues.